Advances in biofeedstocks and biofuels. - Singh, Lalit Kumar; Chaudhary, Gaurav (John Wiley & Sons ; Scrivener Publishing, 2017)
This volume focuses on the production of biofuel, covering all of the major biofuels, such as biodiesel, biohydrogen, bioethanol and others. It touches on all of the most important new processes and technologies, providing the most up-to-date coverage of the science available to industry.